Experimental Investigation of a Modified NOLM for Phase-Encoded Signal Regeneration - Cvecek, Kristian; Onishchukov, Georgy; Sponsel, Klaus; Striegler, Arne; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2006)
We experimentally investigate the amplitude and phase transfer characteristics of a modified nonlinear optical loop mirror (NOLM) with a directional attenuator (DA-NOLM) optimized for differential phase-shift keying signal regeneration. The results show that the phase relation is preserved in the setup and thus the DA-NOLM is suitable for amplitude regeneration of phase-shift-keyed signals. © 2006 IEEE.
UnivIS-Import:2015-04-14:Pub.2006.tech.IE.LEH.experi
Keywords: 2R regeneration; All-optical regeneration; Differential phase-shift keying (DPSK); Nonlinear optical loop mirror (NOLM)